Find the inverse function of h(x) = -2/3x + 6.
2 answers:
<u>Answer:</u>
<u>Step-by-step explanation:</u>
We are given the following function and we are to find the inverse of this function:
For that, we will put the function equal to another variable and make the subject of the function.
Making the subject:
Therefore, the inverse h'(x) = .
Answer:
Step-by-step explanation:
To find inverse of a function, follow the steps below:
1. replace h(x) with y
2. Interchange x and y
3. Solve for the new y
4. Replace y to (this is the inverse function)
<u>Step 1:</u> y = -2/3x+6
<u>Step 2:</u> x = -2/3y+6
<u>Step 3:</u>
<u>Step 4:</u>
This is the inverse function.
You might be interested in
2 x (5-2)^3
2 x (3)^3
2 x 27
54
Step-by-step explanation:
91-19=72
72/2=36
36+19=55=Drama Club students
36 =Yearbook Club Students
Answer:
52/3
Pretty simple just multiply 26 to the 2 and put the 3 to the bottom.
Answer:
the second option
Step-by-step explanation: